Pengembangan Media Evaluasi Pembelajaran Berbasis Android di Madrasah Aliyah Negeri Pontianak - Danar Santoso; Ridho Dedy Arief Budiman (PT. Media Edukasi Borneo, 2021)
This study aimed to develop an android-based learning evaluation tool in one of the state madrasah aliyah in Pontianak. The method used in this research was design-based research (DBR) with the ADDIE framework. Participants in the research in this study were 35 students and 2 practitioners. All instruments were validated by 4 experts. The data were gathered through interviews, observations, and questionnaires. The results showed that the developed android-based learning evaluation tool called MAI was feasible to use, namely it was included in the criteria range